2018
DOI: 10.1159/000492158
|View full text |Cite
|
Sign up to set email alerts
|

Order of Treatment Matters in Ischemic Stroke: Mechanical Thrombectomy First, Then Carotid Artery Stenting for Tandem Lesions of the Anterior Circulation

Abstract: Background: One endovascular treatment option of acute ischemic stroke due to tandem occlusion (TO) comprises intracranial thrombectomy and acute extracranial carotid artery stenting (CAS). In this setting, the order of treatment may impact the clinical outcome in this stroke subtype. Methods: Retrospective analysis was performed on data prospectively collected in 4 international stroke centers between 2013 and 2017. One hundred sixty-five patients with anterior TO were treated by endovascular therapy. Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 37 publications
4
34
1
1
Order By: Relevance
“…Our findings are in most parts in line with the results of other groups [15][16][17][18][19], however, they differ regarding the issue of antegrade versus retrograde stenting. The STRATIS collaboration group [15] demonstrated equipoise concerning antegrade vs. retrograde stenting in a prospective, non-randomized mutlicentric study with 147 patients.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are in most parts in line with the results of other groups [15][16][17][18][19], however, they differ regarding the issue of antegrade versus retrograde stenting. The STRATIS collaboration group [15] demonstrated equipoise concerning antegrade vs. retrograde stenting in a prospective, non-randomized mutlicentric study with 147 patients.…”
Section: Resultssupporting
confidence: 90%
“…The STRATIS collaboration group [15] demonstrated equipoise concerning antegrade vs. retrograde stenting in a prospective, non-randomized mutlicentric study with 147 patients. In contrast, Maus, et al analysed the longterm outcome of one hundred patients after endovascular treatment of tandem lesions and found that the retrograde strategy yielded a significantly higher rate of successful reperfusion and a higher rate of favourable clinical outcome after 90 days [16]. This might be explained in parts by a faster recanalization of the intracranial vessel occlusion, when the extracranial stenosis or occlusion of the ICA is initially treated by PTA only.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the authors did not adjust for baseline ischemic core size. Recently, a matched analysis of 100 patients demonstrated improved reperfusion rates and clinical outcomes in patients treated with the Head-First as compared to the Neck-Frist approach [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests higher final successful reperfusion rates for long stent retrievers in the anterior circulation and higher final complete reperfusion rates for short stent retrievers in the posterior circulation. Final reperfusion rates are known to be affected by the implementation of various technical maneuvers, device properties, and potential adjuvant techniques [12, 19, 22]; the interpretation of the current results should take this into account, although we tried to balance the analysis by appropriate statistical methods.…”
Section: Discussionmentioning
confidence: 99%